Revenue Forecasting-How is it done? : Results from a Survey of Low-Income Countries - Kyobe, Annette; Danninger, Stephan (Washington, D.C. : International Monetary Fund, 2005)
This paper takes stock of revenue forecasting practices in low-income countries, and provides a comprehensive and condensed account of the revenue forecasting process. Based on a new dataset on 34 low-income countries, it catalogues forecasting practices and procedures from inception until budget submission, focusing primarily on institutional aspects and processes. The paper also synthesizes three key characteristics of forecasting practices, formality, organizational simplicity, and transparency, and empirically explores their determinants. High levels of country corruption are associated with less formal and less transparent forecasts. Past IMF involvement in a country increases the formality of the process, but does not improve public access to information.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet